Vaginal 11-point and volumetric dose related to late vaginal complications in patients with cervical cancer treated with external beam radiotherapy and image-guided adaptive brachytherapy - Dankulchai P. (2023)
Objective: To investigate the vaginal 11-point and volumetric dose-toxicity relationships in definitive cervical cancer radiotherapy. Methods: A retrospective cohort study of patients with cervical cancer with a complete response of at least 12 months was performed. Additional per vaginal examinations and patient-scoring questionnaires on the date of patient enrolment were assessed for vaginal strictures. Retrospective dosimetric analysis of vaginal 11-point and volumetric doses was performed with descriptive and probit analyses to investigate dose-toxicity relationships. Results: Ninety-seven patients were included in the study, with a 20-month median follow-up. The incidence rate of grade 3 vaginal strictures was 22.7%. A comparison between patients with grade 1–3 vaginal strictures revealed significant differences in age, stage, initial tumour size, and vaginal involvement. PIBS + 2, PIBS, PIBS-2, D + 5, and D2cc were all significantly different among grade 1–3 vaginal strictures and showed significant probit coefficients. The lateral dose points were significantly higher in grade 2 strictures, but negative probit coefficients failed to establish causal inferences. Post-estimation analyses yielded effective doses (ED) for 15% and 20% probability of grade 3 vaginal strictures (ED15 and ED20) for PIBS + 2 at 57.4 and 111 Gy3, respectively. PIBS-2 yielded an ED20 of 7 Gy3. D + 5 yielded positive ED10, ED15, and ED20 values of 52.2, 66.6, and 78 Gy3, respectively. Conclusions: This study showed a significant relationship between age, tumour size, and lower-third vaginal involvement with the incidence of vaginal toxicity. The goal of a cumulative radiotherapy dose of ≤ 55 Gy3 to PIBS + 2, ≤5 Gy3 to PIBS-2, and ≤ 65 Gy3 to D + 5 points may reduce the risk of grade 3 vaginal stenosis to less than 15–20%.